Check please! eaudiobook - Stern, AJ (Frankly, Frannie, 2012)
Fan-favorite author A.J. Stern is well known for her popular Frankly, Frannie books starring a young girl who loves offices. In this third hilarious installment, Frannie notices the slow service at the opening night of a local restaurant. Her eyes always open for employment opportunities, Frannie decides to help out. But her plan for landing a permanent job vanishes when she realizes that the restaurant serves snails. Now, Frannie knows it's up to her to warn the customers.